Analysis of the Factors that Influence the Work Spirit of Teacher - Cindy Aurora; Robin Robin (Almana : Jurnal Manajemen dan Bisnis, 2022)
The working spirit of teachers at the Anugerah Harapan Bangsa school has decreased. This can be seen in the teachers who feel lazy and less effective in doing their work and do not give satisfaction to parents and students. This study aims to determine whether there is a relationship between compensation, work motivation, and organizational culture in the work spirit of teachers at Anugerah Harapan Bangsa school. The sample in this study amounted to 64 teachers, where the data were obtained directly by filling out a questionnaire in the form of a questionnaire and processed by the Likert scale method. The data method technique used quantitative analysis and multiple linear regression analysis. The results showed that compensation had a positive and significant effect on the work spirit of Anugerah Harapan Bangsa school teachers by 0.000 < 0.05, work motivation had a positive and significant effect on the work spirit of Anugerah Harapan Bangsa school teachers by 0.016 < 0.05, organizational culture had a negative effect on the work spirit of Anugerah Harapan Bangsa school teachers by 0.826 > 0.05, but simultaneously or Simultaneously, compensation, work motivation, and organizational culture have a positive and significant effect on the work spirit of teachers at Anugerah Harapan Bangsa school by 0.000 < 0.05.